Introduction - field methods in ‘closed contexts’: undertaking research in authoritarian states and places - Koch, Natalie (Area, 2013)
This special section on field methods in authoritarian states and places aims to move beyond the normative language of the liberal/illiberal binary by foregrounding the ways in which closure can be an authoritarian act. Illustrating the variety of scales and places at which these practices unfold, the contributors are concerned with what implications they have for conducting geographic fieldwork. The main questions raised by this set of papers are: how is research in ‘closed contexts’ different from (or similar to) more ‘open’ settings? Does it raise unique ethical and methodological dilemmas? In what ways are field methods themselves informed by particular notions of power, agency, and freedom, and how might these differ between more- or less-closed settings? This article first provides some theoretical contextualization, before then introducing how each author variably highlights these themes through a critical reflection on their own experiences of conducting fieldwork in closed contexts, ranging from Vietnam to Kazakhstan, Mozambique, and the United States.